Pre-Columbian graphic. The validity of the past in the processes of contemporary visual creation, a personal vision. DOI: 10.37785/nw.v3n2.a11 - Soto Chávez, Billy Gustavo; Sánchez Mosquera, Fernanda Anaís (Nawi, 2019)
This document makes a brief tour of various criteria regarding the pre-Columbian graphic, its classifications and meanings. It also presents four different visions but linked to the same goal, how the processes of contemporary visual creation linked to pre-Columbian concepts and graphics have been addressed. Finally strategies and methodologies are proposed, some systematic and others random in the resolution of a plastic work that is a reflection of that process that links our graphic legacy and contemporaneity.